Synthesis, anticancer evaluation, and electrochemical investigation of new chiral pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine sulfonamides - Mateusz Kciuk; Gabriela Machura; Somdutt Mujwar; Beata Marciniak; Kamila Koszelska; Sylwia Smarzewska; Mariusz Mojzych; Renata Kontek (Scientific Reports)
Abstract Pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine sulfonamides (MM-compounds) represent a novel class of heterocyclic compounds with promising anticancer potential. In this study, we report the synthesis and biological evaluation of two enantiomeric derivatives: the R-enantiomer (MM124) and the S-enantiomer (MM125). Both compounds exhibited potent and selective cytotoxicity against a panel of cancer cell lines derived from various tissue types, with a median IC₅₀ value of 0.35 µM. Mechanistic investigations in colorectal (HT-29) and prostate (PC-3) cancer cell lines demonstrated that the compounds induce apoptosis, oxidative stress, and DNA damage. Electrochemical assays and computational studies further suggested that MM124 and MM125 interact with DNA. Additionally, in silico pharmacokinetic and toxicological profiling indicated favorable drug-like properties. These findings support the potential of MM124 and MM125 as candidates for the development of new anticancer agents, warranting further structural optimization and preclinical evaluation.